Dynamics in Aceh and North Sumatera after the Twin Disasters: An Investigation into the Relevance of the Locational Fundamental Theory - Aloysius Gunadi Brata; Henri L.F. de Groot; Piet Rietveld (Tinbergen Institute, 2013)
This paper analyzes the impact of the Indian Ocean Tsunami in 2004 and the Nias earthquake in 2005 on population dynamic across regions in Aceh and North Sumatera. We find no evidence that the disasters affected the regularity of size-distribution of the regions. The estimates of a population growth model yield clear evidence that the disasters had only a temporary impact. This study provides indicative evidence for the relevance of the locational fundamental theory and rejects the random growth explanation.
Keywords: R11; R12; Q54; 330; natural disaster; population growth; rank-size distribution